Advanced Coatings for Corrosion Protection - Fürbeth, Wolfram (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Corrosion is a significant issue in many industrial fields. Among other strategies, coatings are by far the most important technology for corrosion protection of metallic surfaces. The Special Issue "Advanced Coatings for Corrosion Protection" has been launched as a means to present recent developments in any type of advanced coating for corrosion protection. This book compiles 15 contributions on metallic, inorganic, polymeric and nanoparticle enhanced coatings that provide corrosion protection as well as other functionalities.